PELAKSANAAN PEMBELAJARAN DI MASA PANDEMI COVID-19 DARI SUDUT PANDANG MAHASISWA DI UNIVERSITAS ISLAM KUANTAN SINGINGI - Dwi Putri Musdansi; Rosa Murwindra; Nofri Yuhelman; Windri Anita (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2022)
This study aims to analyze the implementation of learning in the Covid-19 era from the preception of student's. This research with a quantitative approach uses a number of samples from Isaac and Micheal. The study population was all UNIKS students in the odd and even semesters of the 2020/2021 academic year. The samples taken were 341 respondents using a significance level of 1%. The sampling technique used is simple random sampling with sampling using SPSS, namely simple sampling. The sample in this study was 65.1% female and 34.9% male. The data collection technique used the "PPC-19 Perception Scale" with five alternative answer choices and the data was collected via google form. The data analysis technique used is by using the percentage formula. From the results of data analysis, it was found that the average percentage of respondents' responses related to the implementation of learning during the Covid-19 period was the largest range of choices: Strongly Agree/Like/Good, Agree/Like/Good, Moderately Agree/Like/Good.